Integrated control of Fusarium wilt of chickpea by solar heating of soil amended with oilseed meals and fungicides - R.R. PANDEY2 and A.K. SRIVASTAVA, A.K. PANDEY1, D.K. ARORA (Indian Phytopathology, 2002)
Soil solarization in combination with oilseed organic residues and the half and full doses of fungicides significantly (P=0.05) reduced the population of F. oxysporum f.sp. ciceris and the incidence of chickpea wilt in field trials in Uttar Pradesh, India. Solarized plus neem oilseed meal amended soil exhibited max. reduction in the population of the pathogen (99.2%), and completely eliminated the chickpea wilt. Solarization in combination with half effective dose of fungicides was found significantly (P=0.05) more effective than the solarized non-amended soils in reducing the inoculum of the pathogen and disease incidence. A positive correlation (r=+0.70 to 0.91; P=0.05 to 0.01) was obtained between the reduction in the population of the pathogen and disease incidence in oilseed meal or fungicides amended solarized soils.